Adaptation to an irrigation water restriction imposed through local governance - Drysdale, Krystal M.; Hendricks, Nathan P. (My University, 2018)
We estimate how farmers adapted to a water restriction imposed through local governance. The restriction imposed a uniform quota on water use with a 5-year allocation and allowed trading of the quota within the restricted area. Our analysis exploits unique micro-level data on irrigated water use, irrigated acreage, and crops. We use a difference-in-differences econometric strategy that also includes farmer-time fixed effects to estimate the response to the restriction, where we exploit water rights between 2 and 5 miles of the policy boundary as a control group. Results indicate that farmers reduced water use by 26% due to the policy with most of the response due to reductions in water use intensity on the same crops rather than through reductions in irrigated acreage or changes in crops. The results imply that the short-run welfare impact of the policy was smaller than a policy that reduces irrigated acreage.
Citation: Drysdale, K. M., & Hendricks, N. P. (2018). Adaptation to an irrigation water restriction imposed through local governance. Journal of Environmental Economics and Management, 91, 150–165. https://doi.org/10.1016/j.jeem.2018.08.002
Keywords: JEL: Q15; JEL: Q25; JEL: Q30